Privatization Policy: Its Economic and Social Impacts - Yadav, Baidya Nath Prasad (Academic Voices: A Multidisciplinary Journal, 2015)
Privatization is one of the major policies to the world for improving the illhealthof national economy. Its primary goal is to reduce the financial burden of government through privatization of all loss makers' public enterprises. Besides this, it also helps to increase the competition among all privatized enterprises to promote productivity and profitability. It makes able to all privatized enterprises to operate freely in context to quality, quantity, taste, design, colour, packaging, pricing, promoting for generating the profit. Consequently, privatized enterprises use full resources, increase productivity, run in profitability, develop rapidly, provide more jobs to unemployed workers with high salary and benefits, pay more taxes to government, raise per capita income, facilitate consumers to select desired products, bear well responses to society. Lastly, nation improves itself economically and socially. This paper embodies the discussion of concept, objectives, methods, impacts and conditions for success of privatization. DOI: http://dx.doi.org/10.3126/av.v4i0.12349 Academic Voices Vol.4 2014: 1-8